Implementasi VRIO Framework untuk Mendeteksi Sumber Daya Unik Dalam Upaya Keberlanjutan Bisnis Kuliner dan Manajemen Keuangan - Yunita Niqrisah Dwi Pratiwi; Milka Susana Theorupun; Donna Setiawati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Competitive advantage is crucial for business continuity in a competitive market. It is not merely a strategy but also a crucial component for creating a successful culinary business. The VRIO (Value, Rarity, Imitability, and Organization) framework can be used to evaluate existing resources and identify competitive advantages. The urgency of this research is to understand the unique potential of the culinary business and its impact on profitability and business sustainability. The purpose of this study is to delve deeper into the unique resources in the culinary business and how applying the VRIO framework can help identify competitive advantages related to business sustainability. The method used in this study is mixed methods analysis (a combination of qualitative and quantitative). The population in this study was restaurants in Boyolali City. The sampling technique used was purposive sampling. The results of the study showed that resources that meet the criteria of Value, Rarity, Imitability, and Organization contribute significantly to the sustainability of culinary business operations. The VRIO Framework successfully identified unique resources such as original recipes and distinctive cooking techniques